Asuhan Keperawatan Medikal Bedah Efektivitas Finger Hold Relaxation Dan Hand Massage Dengan Minyak Terapi Terhadap Intesitas Nyeri Pada Pasien Post Apendiktomi Di Ruang Dahlia RSUD Dr. T.C Hillers Maumere - Bernada Silvana Yohanista; Fransiska Ronalia (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Unhealthy eating patterns can cause appendicitis and appendicitis can occur at any age, the way to overcome this is by carrying out surgery or an appendectomy. The consequences of this surgery can cause pain. One way to reduce pain is by using finger hold relaxation and hand massage techniques. The aim of this case study is to determine the reduction in pain scale in post-appendectomy patients after finger hold relaxation and hand massage therapy. The method used in this case study is case study design with a nursing care process approach. The subjects in this case study were 2 patients, obtained from inclusion and exclusion criteria, data collection using the Numerical Rating Scale (NRS). The results of the case study show that the average pain level of the two patients after being given finger hold relaxation and hand massage therapy intervention for 2 days experienced a change from moderate pain to mild pain. The conclusion of this case study shows that there were changes that occurred after the finger hold relaxation therapy intervention and hand massage using therapeutic oil were given to the two patients and they experienced a decrease in the pain scale.